Fake news in digital cultures : technology, populism and digital misinformation - Cover, Rob; Haw, Ashleigh; Thompson, Jay Daniel (Emerald Publishing Limited, 2022)
Fake News in Digital Cultures presents a new approach to understanding disinformation and misinformation in contemporary digital communication, arguing that fake news is not an alien phenomenon undertaken by bad actors, but a logical outcome of contemporary digital and popular culture, conceptual changes meaning and truth, and shifts in the social practice of trust, attitude and creativity. Looking not to the problems of the present era but towards the continuing development of a future digital media ecology, the authors explore the emergence of practices of deliberate disinformation. This includes the circulation of misleading content or misinformation, the development of new technological applications such as the deepfake, and how they intersect with conspiracy theories, populism, global crises, popular disenfranchisement, and new practices of regulating misleading content and promoting new media and digital literacies.